Lost In Jerusalem - Akinseye, Sola (Literamed Publications Nigeria Limited, 2008)
This is the story of the first pass over festival Jesus attends at the age of 12. He is so fascinated by all he sees and hears in God's house,he forgets to join the caravan back home.
Keywords: Christianity; Bible Stories; Religion